PERSAMAAN DIFERENSIAL LINIER TAK HOMOGEN (Universitas PGRI Sumatera Barat, 2018)
ABSTRACTThe mathematical equation can not be separated from everyday life. A mathematical equations need to be analyzed. Persamaanya shape one of which is a differential equation. One form of the equation is a differential equation. In everyday environments are a mathematical model of a differential equation problem. To model a mathematical problem must use the facts. Differential equation is an equation containing the function or derivative. Linear ordinary differential equation is not homogeneous can be converted into homogeneous differential equation if it is reduced.Keywords: differential equations, mathematical models.